Characterization of Enzymes Catalyzing Transformations of Cysteine S‐Conjugated Intermediates in the Lincosamide Biosynthetic Pathway. (19th July 2016) - Ushimaru, Richiro; Lin, Chia‐I; Sasaki, Eita; Liu, Hung‐wen
Abstract: Lincosamides such as lincomycin A, celesticetin, and Bu‐2545, constitute an important group of antibiotics. These natural products are characterized by a thiooctose linked to al ‐proline residue, but they differ with regards to modifications of the thioacetal moiety, the pyrrolidine ring, and the octose core. Here we report that the pyridoxal 5′‐phosphate‐dependent enzyme CcbF (celesticetin biosynthetic pathway) is a decarboxylating deaminase that converts a cysteine S ‐conjugated intermediate into an aldehyde. In contrast, the homologous enzyme LmbF (lincomycin biosynthetic pathway) catalyzes C−S bond cleavage of the same intermediate to afford a thioglycoside. We show that Ccb4 and LmbG (downstream methyltransferases) convert the aldehyde and thiol intermediates into a variety of methylated lincosamide compounds including Bu‐2545. The substrates used in these studies are the β‐anomers of the natural substrates. The findings not only provide insight into how the biosynthetic pathway of lincosamide antibiotics can bifurcate to generate different lincosamides, but also reveal the promiscuity of the enzymes involved. Abstract : Tracing steps in lincosamide synthesis : The functions of two related PLP‐enzymes, CcbF and LmbF, in the lincosamide biosynthetic pathways are characterized. By combining downstream methyltransferases, Ccb4 and LmbG, several lincosamide products were generated.